2018
DOI: 10.1159/000494056
|View full text |Cite
|
Sign up to set email alerts
|

Relation between Early Over- and Undertreatment and Behavioural Problems in Preadolescent Children with Congenital Hypothyroidism

Abstract: Objective: Congenital hypothyroidism (CH) per se, when not treated or undertreated, may lead to severe behavioural problems (cretinism), whereas overtreatment of CH seems associated with attention problems. Design and Methods: For 55 CH patients, prospectively followed from birth until 11 years, parents rated the Child Behaviour Checklist and teachers the Teacher’s Report Form at children’s ages 6 and 11 years. We related scores regarding Attention, Delinquency, and Aggression (ADA scores, indicative for atten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
31
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(35 citation statements)
references
References 28 publications
0
31
0
1
Order By: Relevance
“…Data on the effects of clearly increased serum (f)T4 concentrations are scarce. In two studies, long-term follow-up after periods of overtreatment during the first 2 years of life suggested a decreased IQ at the age of 11 years, and an increased rate of attention deficit hyperactivity disorder ( 108 , 109 ). Earlier studies suggested adverse effects on attention span ( 110 ).…”
Section: Treatment and Monitoring Of Chmentioning
confidence: 99%
“…Data on the effects of clearly increased serum (f)T4 concentrations are scarce. In two studies, long-term follow-up after periods of overtreatment during the first 2 years of life suggested a decreased IQ at the age of 11 years, and an increased rate of attention deficit hyperactivity disorder ( 108 , 109 ). Earlier studies suggested adverse effects on attention span ( 110 ).…”
Section: Treatment and Monitoring Of Chmentioning
confidence: 99%
“…Current guidelines do not recommend treatment of THoP in the absence of elevated TSH [3], particularly keeping in mind the deleterious effects of overtreatment on neurocognition [4]. Also, due to the frequent finding of delayed TSH rise in preterms, guidelines recommend a Bsecond screen^in TSH based NBS programs, at the age of 2 to 4 wk, so as not to miss true CH in preterms [3,5].…”
mentioning
confidence: 99%
“…Overtreatment is a possibility (and occurs in 20% of adults taking levothyroxine [9]). Although the pediatric data have been quite limited, there is some evidence that overtreatment of congenital hypothyroidism, at least during infancy, can have adverse cognitive effects [10].…”
mentioning
confidence: 99%